Potential Therapeutic Effect and Mechanisms of Mesenchymal Stem Cells-Extracellular Vesicles in Renal Fibrosis - Liao, Chunling; Chen, Guangyong; Yang, Qian; Liu, Yiping; Zhou, Tianbiao (Frontiers in Cell and Developmental Biology, 2022)
Renal fibrosis (RF) is central pathological pathway for kidney diseases, with the main pathological features being the aberrant accumulation of myofibroblasts that produce accumulation of extracellular matrix in the renal interstitium and glomeruli. Acute kidney injury (AKI) and chronic kidney disease (CKD) are associated with RF. Current treatment strategies for RF are ineffective. Mesenchymal stem cells (MSCs) have been found to be able to treat organ fibrosis including RF, but they have some safety problems, such as cell rejection, carcinogenicity, and virus contamination, which limit the application of MSCs. However, current studies have found that MSCs may exert their therapeutic effect by releasing extracellular vesicles (EVs). MSC-EVs can transfer functional proteins and genetic material directly to the recipient cells. As non-cell membrane structures, MSC-EVs have the advantages of low immunogenicity, easy preservation, and artificial modification, but do not have the characteristics of self-replication and ectopic differentiation. Therefore, EVs are safer than MSCs for treatment, but might be less effective than MSCs. Recent studies have also found that MSC-EVs can improve renal function and pathological changes of RF. Thus, this review summarizes the therapeutic effect of MSC-EVs on RF and the mechanisms that have been discovered so far, so as to provide a theoretical basis for the further study of the role of MSC-EVs in treating RF diseases.